Prophylactic subcutaneous retention sutures in the prevention of superficial wound separation of midline laparotomy. Issue 9 (September 2021) - Iltar, Elif; Ureyen, Isin; Toptas, Tayfun; Doğan, Selen; Uysal, Aysel
Abstract : Objectives: This prospective study aimed to determine the effectiveness of prophylactic subcutaneous retention sutures in the prevention of superficial wound separation in women with a confirmed or suspected cancer who had gynecological surgery by midline laparotomy. Methods: This was a non-randomized, controlled intervention study including patients who underwent cancer surgery between May 2018 and August 2019. Patients who underwent midline laparotomy with confirmed or suspected cancer were included and patients who had an early post-operative complication or who underwent surgery again before the removal of stitches were excluded. The independent variables that might predict the superficial wound site dehiscence and prolongation of the hospitalization period were analyzed using logistical regression analysis. Results: A total of 208 patients were included in the study. Age, presence of comorbid diseases, low pre-operative hemoglobin, low pre-operative albumin, higher weight, higher body mass index (BMI), pre- and post-operative blood transfusion, and absence of retention sutures were associated with higher risk of superficial wound separation. Low pre-operative albumin, weight, and BMI were associated with prolonged length of hospital stay. In a multivariate analysis, BMI (OR: 1.12; 95% CI: 1.09 to 1.28, p<0.001) and retention sutures (OR: 0.31; 95% CI: 0.11 to 0.83, p=0.019) retained an independent association with superficial wound separation. In addition, BMI (OR: 1.11; 95% CI: 1.03 to 1.25, p=0.010) and intra-operative complications (OR: 4.10; 95% CI: 1.08 to 15.60, p=0.038) were independent predictors increasing the length of hospital stay, and use of retention sutures (OR: 0.19; 95% CI: 0.05 to 0.66, p=0.009) was an independent predictor decreasing the length of hospital stay. Conclusions: Prophylactic subcutaneous retention sutures reduced superficial wound separation and shortened hospital stay. Prophylactic subcutaneous retention sutures may be considered in patients who undergo gynecological surgery using a midline laparotomy.